Structural insights of ZIP4 extracellular domain critical for optimal zinc transport - Tuo Zhang (Nature Portfolio, 2016)
Mutations in the extracellular domain of zinc transporter ZIP4 result in a lethal disorder. Here, the authors report the first crystal structure of ZIP4 extracellular domain, unveiling its unprecedented dimerization and two structural independent subdomains that have crucial roles in zinc transport.